2014
DOI: 10.1002/hep.27159
|View full text |Cite
|
Sign up to set email alerts
|

Binding of hepatitis B virus to its cellular receptor alters the expression profile of genes of bile acid metabolism

Abstract: Chronic hepatitis B virus (HBV) infection has been associated with alterations in lipid metabolism. Moreover, the Na 1 -taurocholate cotransporting polypeptide (NTCP), responsible for bile acid (BA) uptake into hepatocytes, was identified as the functional cellular receptor mediating HBV entry. The aim of the study was to determine whether HBV alters the liver metabolic profile by employing HBV-infected and uninfected human liver chimeric mice. Humanized urokinase plasminogen activator/severe combined immunode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 34 publications
6
121
0
1
Order By: Relevance
“…On the other hand, interactions between viral components and cellular factors may also impact the liver metabolism. Recent studies showed that binding of the preS1 domain of the large envelope protein of HBV limits the hepatocellular uptake of bile salts [79,80] and the expression profile of key genes involved in bile acid metabolism [81]. These findings suggest that in the setting of chronic HBV infection, alterations of the hepatocellular uptake of bile acids may lead to different levels of compensatory metabolic alterations and also promote disease progression.…”
Section: Factors Involved In Disease Progression and Carcinogenesismentioning
confidence: 89%
“…On the other hand, interactions between viral components and cellular factors may also impact the liver metabolism. Recent studies showed that binding of the preS1 domain of the large envelope protein of HBV limits the hepatocellular uptake of bile salts [79,80] and the expression profile of key genes involved in bile acid metabolism [81]. These findings suggest that in the setting of chronic HBV infection, alterations of the hepatocellular uptake of bile acids may lead to different levels of compensatory metabolic alterations and also promote disease progression.…”
Section: Factors Involved In Disease Progression and Carcinogenesismentioning
confidence: 89%
“…1e). HBV Pre-S1 engagement of NTCP has been reported to alter the expression of genes involved in bile acid metabolism (Oehler et al, 2014), and these pathways may play a role in promoting the assembly and/or secretion of pseudoparticles.…”
mentioning
confidence: 99%
“…The (metabolic) consequences of this action are currently not clear, although some first insights were obtained using a mouse model, where human hepatocytes repopulated the liver of urokinase plasminogen activator/severe combined immunodeficiency mice. NTCP inhibition using myrcludex B resulted in increased CYP7A1 expression, suggesting reduced FXR activity [82]. Chronic HBV infection in these humanized mice had a similar effect.…”
Section: Bile Acid Dynamics In Relation To the Metabolic Statementioning
confidence: 84%